La Fleur as Feminine Archetype in Le Petit Prince (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
This research is about the representation of women through anthropomorphism in Le Petit Prince by Saint - Exupéry (1943). It focuses on the figurative character of a feminine archetype. Previous studies on anthropomorphism focused on unseen meanings, metaphor categorization, and the application of animals and natural entities to portray human behaviour, specifically women. The recent research has a goal to seek how La Fleur depicts women, feminine characteristics, and patriarchal values in the French culture. The data are taken from Le Petit Prince in its original French version. This research is under the cognitive semantics field and uses the conceptual metaphor theory. This article solely focuses on ontological metaphor since it primarily observes how human characteristics are transferred to a non – human entity. A qualitative descriptive method is applied to examine the data. La fleur works as an anthropomorphic metaphor imaging women’s feelings, attitudes, behaviour, thoughts, and fragility. The representations reveal cultural principles and a patriarchal point of view where women are subtle and dependent in society’s perspective, and all their actions are motivated by emotions. This research commits to cognitive metaphor by presenting how anthropomorphism in Le Petit Prince emphasize culturally impacted structures of femininity inside French Society.
Keywords: Anthropomorphism; French Culture; Ontological Metaphor